A hardware-efficient technique to implement a trellis code modulation decoder. - Dinh, A.
This brief presents a new technique in implementing a very large-scale integration trellis code modulation (TCM) decoder. The technique aims to reduce hardware complexity and increase decoding throughput. The technique is introduced in the design of a Viterbi decoder. To simplify the decoding algorithm and calculation, branch cost distances are pre-calculated and stored in a distance look-up table (DLUT). The concept of DLUT significantly reduces hardware requirements as this table eliminates the need for calculation circuitry. In addition, an output LUT (OLUT) is constructed based on the trellis diagram of the code. This table generates the decoding output using information provided by the algorithm. The use of this OLUT reduces the amount of storage requirement. The technique was used to design a 16-state, radix-4 codec for two-dimensional and four-dimensional TCM. The decoder was implemented in hardware after functional simulation. The tested ASIC has a core area of 1.1 mm2 in 0.18-μm CMOS. A decoding speed of 1 Gbps was achieved. Implementation results have shown that LUTs can be used to decrease hardware requirement and increase decoding speed.
Keywords: 0.18 micron; 1 Gbit/s.; ASIC; CMOS; VLSI; Viterbi decoder; Decoding algorithm; Decoding throughput; Distance look-up table; Hardware complexity; Hardware-efficient technique; Trellis code modulation decoder; Trellis diagram